Gaya Bahasa Humoris Selebgram Aceh @khaliltoktok - Marensha Erensi; Meri Yulizar; Intan Munawarah; Hasanah Hasanah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
This study aims to describe the style of humorous language in the social media account @khaliltoktok. This research used a qualitative approach with descriptive methods. The data sources for this research are Instagram, YouTube, and TikTok. The data in this study are in the form of oral data and are verbal in nature, namely sentence construction that shows a humorous style of language. Data collection techniques using recording techniques, observation, and note-taking techniques. The data analysis technique consists of three stages, reduction, classification, presentation, and conclusions. The results of the study show that in the social media account @khaliltoktok there are four types of figurative language that generate humorous effects, namely (1) repetition of figurative language consisting of anaphora, tautotes, simploke, epistrophora, and mesodiplosis; (2) comparative figurative language consisting of similes, personifications, pleonasms or tautologies, and antitheses; (3) linking language style consisting of eponyms, euphemisms, asindenton, polysindenton; and (4) conflicting language style consisting of hyperbole hysteron proteron, cynicism, and sarcasm. Creative use of various language styles can create various humorous effects and provide a distinctive style of communication